The Association Between Employees' Perspectives on CSR and their Commitment to The Organizations in The Hospital Settings - Younas, Asifa; Saleem, Kashif (Archives of Business Research, 2024)
There need to be more studies on how corporate social responsibility (CSR) affects personnel and Organizational Commitment (OC), even though many academics have examined the effects of CSR in various organizational situations. This study explores the relationship between hospital staff members' perceptions of CSR and OC in light of this research gap. The problem is addressed by this quantitative correlational study, which uses the social identity theory (SIT) as its conceptual framework. According to the theory, workers with higher CSR ratings will also have higher OC scores. The independent variables cover Four CSR dimensions: CSR toward consumers, CSR toward workers, and CSR toward the government. The community is the target of CSR. OC is the dependent variable. Hospitals in Pakistan were the source of research participants. The data analysis phase demonstrated a statistically significant positive association between hospital employees' views of OC and CSR. To detect any patterns or distinctions in how workers see CSR and its influence on OC, future research may want to replicate this survey with staff members from various departments and compare the results.